Assessment of a Cattle Manure Vermicomposting System Using Material Flow Analysis: A Case Study from Uganda - Jjagwe, Joseph; Komakech, Allan John; Karungi, Jeninah; Amann, Arabel; Wanyama, Joshua; Lederer, Jakob (Sustainability, 2019)
Growth in cattle population is associated with increased manure generation whose current management in low-income countries is associated with health and environmental problems as well as low utilization rates. This trend can be reversed by promoting better manure management technologies. This study assessed vermicomposting as one of the technologies to manage organic wastes, using the case study in Uganda. A vermicomposting system using cattle manure and earthworms (Eudrilus euginea) was monitored for one year with the harvesting of products (compost, earthworm biomass) after every three months. Vermicompost samples from the beginning of the experiment and after every harvest were analyzed for the following parameters: pH, ash content, volatile and total solids, nutrients N, P, K, and C. Emissions of CO2, CH4, NH3, and N2O were also measured. Material flow analysis was used to determine the flows and retention of nutrients within the system. Results showed that total solids, ash, N, P, and K content significantly increased, while contents of volatile solids and C, as well as the pH, significantly decreased over time. Of the materials that entered the vermicomposting system, 46% went to vermicompost, 2% into earthworms, and 52% was lost to the atmosphere. Substance flow analysis showed that 30% of C went to vermicompost, 69% was emitted to the atmosphere, and 2% ended up in earthworms while 75% of N was transferred to vermicompost, 7% went to earthworms, and 18% escaped into the atmosphere. The cumulative emissions were 102 g CO2 kg􀀀1 waste, 7.6 g CH4 kg􀀀1 waste, and 3.943 10􀀀5 g N2O kg􀀀1 waste on a dry basis, while NH3 was not detected throughout the measurement time. Compared to other manure management methods, vermicomposting demonstrated good potential in conserving nutrients as well as reducing greenhouse gas emissions.
Keywords: Vermicomposting; Cattle manure; Material flow analysis; Greenhouse gases